New Boundaries Between Aging, Cognition, and Emotions - Alberto Di Domenico (Frontiers Research Topics, 2018)
Numerous studies have reported age-related differences for emotional information. For example, when, compared to younger adults, older adults reveal a relative preference in attention and memory for positive over negative information. One explanation places emphasis on an emotion processing preference in older adults that reflects their socioemotional self-relevant goals. Based on evidence from behavioral and neuroscientific research, researchers have realized that it is necessary to propose a new conceptual framework to describe the relationship between cognition and emotion. Given the growing body of research focused on the interaction between emotions and cognition, our purpose is to provide a picture of the state of the art of the interaction between aging, cognition and emotions.